Cover Feature: Anthraquinone Derivative Reduces Tau Oligomer Progression by Inhibiting Cysteine‐Cysteine Interaction (ChemistryOpen 5/2019) - Areche, Carlos (ChemistryOpen, 2019)
The Cover Feature shows a new derivative anthraquinone isolated from Lichen Xanthoria ectaneoides (Nyl.) Zahlbr, which can reduce progression of oligomers of tau protein involved in neurodegenerative disorders such as Tauopathies. Considering that adults are increasing in number and that current treatments are only palliative, it is crucial to considerer new compounds as a scaffold for drug development. More information can be found in the Communication by C. Areche et al. on page 554 in Issue 5, 2019 (DOI: 10.1002/open.201800222).[Image: see text]